Open Surgery for Osteoid Osteoma with Three Dimensional C‐arm Scan under the Guidance of Computer Navigation. Issue 2 (7th July 2016) - Lin, Nong; Ye, Zhao‐ming; Qu, Hao; Yan, Xiao‐bo; Pan, Wei‐bo; Huang, Xin; Liu, Meng
Abstract : Objective: To evaluate the clinical outcomes of open surgery for osteoid osteoma with three‐dimensional (3‐D) C‐arm scan under the guidance of computer navigation. Methods: The clinical data of 14 patients who had undergone 3‐D C‐arm scan under the guidance of computer navigation during open surgery for osteoid osteoma from March 2012 to June 2015 were analyzed retrospectively. There were nine male and five female subjects aged from 9 to 55 years (mean, 26 years). Eight of the tumors were located in the femur, four in the tibia, one in the humerus and one in the scapula. Preoperative pain visual analogue scale (VAS) scores ranged from 2 to 6 (mean ± SD, 4.7 ± 1.1). Conventional surgical approaches were used to expose the tumor surfaces depending on their locations. Involved regions were scanned by 3‐D C‐arm fluoroscopy during the procedure and then the tumors were accurately located and their niduses removed under the guidance of computer navigation. Afterwards, repeat 3‐D C‐arm scans of the surgical region were performed to confirm tumor eradication. None of the patients received postoperative intravenous analgesia. Eight patients received oral non‐steroidal anti‐inflammatory drugs on the day of surgery, these drugs being discontinued on the second postoperative day. Postoperative pathological diagnoses were recorded. At the follow‐up visits, imaging and VAS scores were obtained to evaluate the therapeutic effect and any evidence of recurrence. Results: All the patients successfully underwent computer navigation‐guided surgery. The duration of surgery ranged from 60 to 135 min (mean, 94 min) and the amount of bleeding from 50 to 150 mL (mean, 80 mL). None of the patients needed bone grafting or internal fixation. No complications were seen. All patients were followed up for 4 to 36 months (mean, 16 months). Postoperative pathological diagnoses of osteoid osteoma were made in 12 patients; thus, the rate of pathologically confirmed diagnosis was 86%. VAS scores decrease to an average of 1.4 ± 0.6 3 days after surgery and were zero for all patients 4 months after surgery. No tumor recurrence was found by X‐ray or CT scan examination during follow‐up. Conclusions: The niduses of osteoid osteomas can be eradicated by open surgery with 3‐D C‐arm scan under the guidance of computer navigation with minimal damage to bone structure and a high rate of pathologically confirmed diagnoses.